Early Mobilization with Digital-Based Isometric Exercise Intervention: Impact on Pain and Muscle Strength Post-ORIF Upper Extremity - Febryandy, Valentino; Gayatri, Dewi; Natashia, Dhea; Jumaiyah, Wati; Yuniarsih, Winda (Jurnal Ners, 2025)
Background Fracture is a condition of partial or complete bone discontinuity. Upper extremity fractures can be caused by direct trauma (such as accidents) or indirect trauma (such as excessive pressure). Fracture management is performed through surgery such as Open Reduction Internal Fixation (ORIF), which can cause pain and muscle stiffness. Early mobilization with isometric exercises is needed to prevent these problems. Objective This study aims to determine the effect of digital-based Isometric Exercise on pain levels and muscle strength in patients post-ORIF upper extremity fracture. Methods The study used a Quasi-Experimental design with a Pretest-Posttest Control Group approach, involving 34 respondents divided into two groups. Muscle strength was measured using a Hand Grip Dynamometer, while pain was measured using the Brief Pain Inventory Short Form (BPI-SF). Isometric exercise intervention was performed 24 hours after surgery, twice daily with a duration of 35 minutes per intervention. Results The study showed a more significant increase in muscle strength in the intervention group compared to the control group with a Mean difference increasing to 4.23 (95% CI: 3.28-5.18), t=9.062, df=32, p=0.000. Pain levels also decreased more in the intervention group with a Mean difference of 1.81 (SD=0.866), 95% CI: 1.51-2.11, t=12.2, df=33, p=0.000. Conclusion: Isometric exercise is effective as early mobilization to reduce pain and increase muscle strength in ORIF upper extremity fracture patients. Keywords: Digital Intervention, Upper Extremity Fracture, Isometric Exercise, Muscle Strength, Pain